Zoonotic diseases associated with pet birds - Seyedeh Alemeh Hosseinian (Journal of Zoonotic Diseases, 2022)
Birds are the most popular pet animals kept by humans in many areas of the world. Budgerigars, Canaries, Lovebirds, and Cockatiels are the most common pet birds. Zoonotic diseases are one of the most critical concerns related to pet birds worldwide. The people at the most risk of zoonoses are immunocompromised patients, veterinarians, pet bird owners, pet bird shops, and workers in pet exhibitions. Zoonotic diseases are transmitted via the fecal-oral, inhalation, and vector-borne routes. Zoonotic pathogens infect humans through direct or indirect contact with infected birds, contaminated birds’ cages, food dishes, or droppings. Several bacterial, viral, parasitic, and fungal zoonoses are known in pet birds. Some zoonoses, such as highly pathogenic avian influenza, salmonellosis, and chlamydiosis, have significant public health risks that lead to serious human diseases. Newcastle disease and giardiasis are minor zoonoses that cause self-limiting infections in humans. Salmonellosis and campylobacteriosis are food-borne zoonoses with global importance in human health. Biosecurity and hygiene, cleaning and disinfecting bird cages, and using human protective equipment can help to control zoonoses in birds and humans.